Invasive crayfish alter the long‐term functional biodiversity of lotic macroinvertebrate communities. (19th August 2020) - Mathers, Kate L.; White, James C.; Guareschi, Simone; Hill, Matthew J.; Heino, Jani; Chadd, Richard
Abstract: Invasive species represent one of the primary threats to global biodiversity. Despite acknowledged implications for taxonomic properties of ecological communities following invasion, functional measures remain poorly understood. We examined the long‐term implications of invasion by a crayfish species, Pacifastacus leniusculus, on functional alpha and beta diversity properties of lotic macroinvertebrate communities in three English regions. The dataset comprised 477 samples collected predominantly between 1990 and 2013. Unlike many invasion studies, we employed before and after invasion comparisons, in association with control rivers not invaded by crayfish. Functional richness and divergence metrics displayed the strongest responses to invasion, highlighting that P. leniusculus may alter the range of functional niches and extreme trait values (likely reflecting resistance and resilience mechanisms) displayed by macroinvertebrate communities. Interestingly, in one region, biodiversity gains seen in control rivers were not mirrored in invaded rivers, potentially suggesting that invasion inhibited ecological improvements. Invasion by signal crayfish resulted in functional compositional changes in two of the three English regions studied, with these rivers yielding greater ecological differences between pre‐ and post‐invasion periods relative to control rivers. This change was primarily driven by higher nestedness values in invaded rivers, with communities containing functional subsets relative to control rivers. The third region demonstrated no functional compositional changes or alterations in functional beta diversity associated with invasion. Our findings indicated that in most instances, the functional properties of macroinvertebrate communities responded to crayfish invasion and may therefore represent a complementary means to monitor the ecological condition of lotic ecosystems. Given their spatial transferability, functional traits could provide a platform to guide regional management practices in the face of biological invasions. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article .